Performance of the CogState computerized battery in the Mayo Clinic Study on Aging - Mielke, Michelle M. (Alzheimers Dement, 2015)
BACKGROUND: The feasibility and validity of brief computerized cognitive batteries at the population-level are unknown. METHODS: Non-demented participants (n = 1660, age 50–97) in the Mayo Clinic Study on Aging completed the computerized CogState battery and standard neuropsychological battery. The correlation between tests was examined and comparisons between CogState performance on the personal computer (PC) and iPad (n = 331), and in the Clinic vs. at home (n = 194), were assessed. RESULTS: We obtained valid data on >97% of participants on each test. Correlations between the CogState and neuropsychological tests ranged from −0.462 to 0.531. While absolute differences between the PC and iPad were small and participants preferred the iPad, performance on the PC was faster. Participants performed faster on Detection, One Card Learning, and One Back at home compared to the Clinic. CONCLUSIONS: The computerized CogState battery, especially the iPad, was feasible, acceptable, and valid in the population.